sistem kontroling biaya dan pemakaian air PDAM berbasis internet of thinks menggunakan wemos d1 dan blynk: Kontroling Biaya dan Pemakaian Air PDAM - ambika, rully; Sudianto (Sekolah Tinggi Ilmu Komputer El Rahma, 2025)
ABSTRACTThe need for clean water is increasing, especially in urban areas, where it is becoming a scarce commodity and has commercial value. The government-owned Drinking Water Company (PDAM), commonly known as the